Suppressing Fermi Acceleration in a Driven Elliptical Billiard - Leonel, Edson Denis [UNESP]; Bunimovich, Leonid A. (Amer Physical Soc, 2010)
We study dynamical properties of an ensemble of noninteracting particles in a time-dependent elliptical-like billiard. It was recently shown [Phys. Rev. Lett. 100, 014103 (2008)] that for the non-dissipative dynamics, the particle experiences unlimited energy growth. Here we show that inelastic collisions suppress Fermi acceleration in a driven elliptical-like billiard. This suppression is yet another indication that Fermi acceleration is not a structurally stable phenomenon.